Psychological impact of COVID‐19 on nurses caring for patients during COVID‐19 pandemic in Gaborone - Kebope Mongie Kealeboga; Esther Ikaege Ntsayagae; Onalenna Tsima (Nursing Open, 2023)
Abstract Aim Nurses as front liners have direct contact with COVID‐19 patients during the pandemic. Carrying the heavy burden during the pandemic has a mental health toll on healthcare professionals. The study explored nurses' experiences of psychological distress during the COVID‐19 pandemic in Botswana's two COVID‐19 special care centres. Design The study used qualitative case study research to solicit nurses' experiences caring for patients with COVID‐19 in selected COVID‐19 centres in Gaborone. Method Researchers purposively recruited nurses from two COVID‐19 centres in Botswana. Data were collected using semi‐structured telephone interviews and analysed through inductive thematic analysis. Various institutional review boards ethically cleared the study. Results Six themes emerged from the thematic analysis: feelings of fear and anxiety, hopelessness and helplessness, loneliness, physical distress, support mechanism and commitment to care. Public Contribution The results offer important insights into the nurses' experiences during the COVI‐19 pandemic.